2020
DOI: 10.3390/nu12020498
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Specific Probiotic Properties of Bifidobacteria and Lactobacilli for the Prevention of Diarrhea Caused by Rotavirus in a Preclinical Model

Abstract: Probiotic supplementation with different lactobacilli and bifidobacterial strains has demonstrated beneficial effects in infectious diarrhea caused by rotavirus (RV) in young children. Preclinical models of RV infection might be a good strategy to screen for the efficacy of new probiotic strains or to test their comparative efficacy. Neonatal Lewis rats were supplemented with Bifidobacterium breve M-16V, Lactobacillus acidophilus NCFM, Lactobacillus helveticus R0052, or Lactobacillus salivarius PS2 from days 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 70 publications
1
29
0
1
Order By: Relevance
“…Previous studies in humans and in our rat model have also shown a disbiosis associated with the infection and have shown how the modulation of the microbiota composition is associated with clinical amelioration [ 46 ]. Specific bacterial strains and particular prebiotics have been shown to improve RV gastroenteritis by both direct and indirect mechanisms, such as pathogen aggregation or immunomodulation, respectively [ 25 , 28 ]. Therefore, gut microbiota sexual dimorphism should also be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in humans and in our rat model have also shown a disbiosis associated with the infection and have shown how the modulation of the microbiota composition is associated with clinical amelioration [ 46 ]. Specific bacterial strains and particular prebiotics have been shown to improve RV gastroenteritis by both direct and indirect mechanisms, such as pathogen aggregation or immunomodulation, respectively [ 25 , 28 ]. Therefore, gut microbiota sexual dimorphism should also be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 23 Lewis pregnant rats obtained from Janvier Labs (Le Genest-Saint-Isle, France) and Harlan (Barcelona, Spain) were used. Animals included in this study were derived from previous independent studies [ 20 , 21 , 25 , 26 ], allowing enough power analysis to draw conclusions. In all cases, gestating rats were housed individually in cages, monitored daily and allowed to deliver at term.…”
Section: Methodsmentioning
confidence: 99%
“…Probiotic supplements with lactobacilli and bifidobacterial strains are well-established as part of the treatment of infectious diarrhea caused by rotavirus. Azagra-Boronat and Massot-Cladera [ 76 ] showed that probiotics decreased the severity and incidence of diarrhea in the preclinical assay. Furthermore, probiotics and their metabolites have been investigated as adjuvants in immunotherapy for viral hepatitis cirrhosis [ 77 ].…”
Section: Probiotics and Immunitymentioning
confidence: 99%
“…Later, in 2017, Park et al [97] reach similar results after administering B. longum BORI and L. acidophilus AD031 to infants infected with rotavirus. A more recent study has proven that specific probiotic strains such as Lactobacillus salivarius PS2, L. acidophilus NCFM, Bifidobacterium breve M-16V, and Lactobacillus helveticus R0052 have the ability to reduce the severity of rotavirus infection [98].…”
Section: Rotavirus Infectionmentioning
confidence: 99%